Habitual Total Drinking Fluid Intake Did Not Affect Plasma Hydration Biomarkers among Young Male Athletes in Beijing, China: A Cross-Sectional Study - Zhang, Jianfen; Zhang, Na; Li, Yibin; He, Hairong; Ma, Guansheng (Nutrients, 2022)
The purposes of this study were to explore the drinking patterns, and urinary and plasma hydration biomarkers of young adults with different levels of habitual total drinking fluid intake. A cross-sectional study was conducted among 111 young male athletes in Beijing, China. Total drinking fluids and water from food were assessed by a 7-day, 24-h fluid intake questionnaire and the duplicate portion method, respectively. The osmolality and electrolyte concentrations of the 24-h urine and fasting blood samples were tested. Differences in groups LD1 (low drinker), LD2, HD1, and HD2 (high drinker), divided according to the quartiles of total drinking fluids, were compared using one-way ANOVA, Kruskal–Wallis H-tests, and chi-squared tests. A total of 109 subjects completed the study. The HD2 group had greater amounts of TWI (total water intake) and higher and lower contributions of total drinking fluids and water from food to TWI, respectively, than the LD1, LD2, and HD1 groups (p < 0.05), but the amounts of water from food did not differ significantly among the four groups (all p > 0.05). Participants in the HD2 group had higher amounts of water than participants in the LD1, LD2, and HD1 groups (p < 0.05); SSBs were the second top contributor of total drinking fluids, ranging from 24.0% to 31.8%. The percentage of subjects in optimal hydration status increased from 11.8% in the LD1 group to 58.8% in the HD2 group (p < 0.05). The HD2 and HD1 groups had 212–227 higher volumes of urine than the LD1 and LD2 groups (p < 0.05). No significant differences were found in the plasma biomarkers (p > 0.05), with the exception of higher concentrations of K in the HD1 group than in the LD1 group (p < 0.05). Subjects with higher amounts of total drinking fluids had better hydration status than those with lower total drinking fluids, but not better drinking patterns. Habitual total drinking fluids did not affect the plasma biomarkers.